How is HOTS integrated into the Indonesian high school English textbook? - Nira Erdiana; Sulastri Panjaitan (Studies in English Language and Education, 2023)
This study aims at analyzing the integration of higher-order thinking skills, specifically the level of analysis (C4), the level of evaluation (C5), and the level of creation (C6), in reading comprehension questions found in senior high school textbook ‘Bahasa Inggris SMA/MA/SMK/MAK for Grade 12’. This study employed critical content analysis to analyze and interpret textual material to draw valid inferences. The researchers examined the reading comprehension questions to find out how the integration of HOTS in the questions. Using a checklist table, the researchers collected, listed, and analyzed the questions according to the cognitive domain of the revised Bloom’s taxonomy. After examining and determining the cognitive level of each question, the researchers categorized them into two groups, namely higher-order thinking skills (HOTS) and lower-order thinking skills (LOTS) questions. The result showed that the distribution of HOTS-level questions was lower than that of LOTS questions. The data show that the number of HOTS questions got 13 out of 67 questions or 19.4%, while LOTS questions reached 54 out of 67 questions or 80.6%. These results imply that this textbook needed to provide an adequate number of higher-level thinking questions that could enhance students’ HOTS. To sum up, HOTS questions were not sufficiently integrated into the reading comprehension questions of the textbook. Thus, it is expected that the findings of this study motivate education stakeholders, including teachers, textbook authors, and publishing houses to make more effort to foster and develop HOTS in textbooks.